The Correlation of Isomorphic, Open-Ended, and Conventional Score on the Ability to Solve Kinematics Graph Questions - Tomy Suganda; Sentot Kusairi; Nur Azizah; Parno Parno (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
isomorphic and conventional to open-ended can reflect students' learning difficulties on kinematic's graphs. This study used a quantitative descriptive form of survey research. The respondents were twenty-nine senior high school students from Semarang. The instruments were adopted from the Test of Understanding Graphs-Kinematic (TUG-K) by Robert J.Beichner (1994). There were nine questions used from the TUG-K with open-ended questions that have been validated. The results show that students have difficulties learning about kinematic's graphs, and there is no relation between open-ended scores and the other two scores. Nonetheless, judging from the correlation coefficient, the correlation between open-ended and conventional tasks is 0.075, which means low correlation, while for isomorphic score and open-ended score in the amount of 0.109 is higher than the correlation of traditional and open-ended. This correlation is insignificant. However, the closest correlation direction to the open-ended test is isomorphic compared to the conventional one. Therefore, it is concluded that isomorphic assessment is more useful than traditional review in kinematic graphics.